Recognizing Opportunities across Campus: The Effects of Cognitive Training and Entrepreneurial Passion on the Business Opportunity Prototype. (4th October 2017) - Costa, Sílvia F.; Santos, Susana C.; Wach, Dominika; Caetano, António
Abstract : We analyze the effects of the program Cognitive Entrepreneurial Training in Opportunity Recognition on the accurate assessment of prototypical viability of business opportunities. The training integrates the principles of experiential learning and is designed to reach students across campus. We also investigate the moderating role of entrepreneurial passion on opportunity recognition learning. We use a quasi‐experimental design with pre‐test, post‐test in two European universities. The results demonstrate that the training has positive significant effects on the accurate identification of business opportunities' prototypical viability. Intense positive feelings about entrepreneurship moderate the learning process. We provide insights into entrepreneurship education practice across campus.